2002
DOI: 10.1007/s00330-002-1319-0
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts in imaging of laryngeal and hypopharyngeal cancer

Abstract: In adjunct to direct laryngoscopy, CT and/or MRI are needed for an accurate staging of laryngeal and hypopharyngeal carcinomas because both cross-sectional imaging modalities are known to reliably evaluate deep tumor infiltration. Except for the clinical background, this article reviews technical aspects of CT and MRI, the pathologic appearance of laryngeal and hypopharyngeal carcinomas, and therapeutically relevant diagnostic aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 34 publications
(57 reference statements)
0
16
0
6
Order By: Relevance
“…3,4 The shapes and sizes of the 34 tumors on sonography were compared with those on CT in similar transverse sections. In a section where a lesion was shown, its maximal size and transverse and posteroanterior dimensions were measured.…”
Section: Imaging Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The shapes and sizes of the 34 tumors on sonography were compared with those on CT in similar transverse sections. In a section where a lesion was shown, its maximal size and transverse and posteroanterior dimensions were measured.…”
Section: Imaging Evaluationmentioning
confidence: 99%
“…Dedicated CT scanning is able to supply valuable information for tumor staging. 3,4 Magnetic resonance imaging also has a great deal of value in showing the hypopharyngeal and laryngeal anatomy in detail and is reported to be more sensitive than CT for detecting minor cartilage invasion. 5 However, CT and magnetic resonance imaging cannot be performed in real time and have limitations when the mobility of the larynx needs to be evaluated.…”
mentioning
confidence: 99%
“…5 Agada et al 6 reported the accuracy of CT staging compared with pathologic specimens, demonstrating that 45% of patients were overstaged and 10% were understaged by CT. Other studies have examined the potential benefits of smaller sections, by using coronal/sagittal and 3D reconstructions and having patients do a variety of breathing maneuvers, including quiet breathing, breath-holding, and modified Valsalva maneuvers. 7 Results in these studies varied, but most found that reconstructions are helpful and that breathing maneuvers improve imaging quality.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for the latter is the presence of artifacts from tooth fillings on CT at the suprahyoid level. The otolaryngologist can easily judge mucosal spread, but imaging is necessary to detect invasion of cartilage and for better assessment of submucosal spread [37]. Spiral CT is standard for imaging head and neck tumors.…”
Section: The First Group: Neoplasmsmentioning
confidence: 99%